Preparation method and application of wear-resistant TPE material for data line
By preparing TPE materials for data cables that combine fluorinated cyclotetrasiloxane with reinforcing monomers and modified fillers, the problem of data cable wear is solved, wear resistance and toughness are improved, and service life is extended.
Patent Information
- Application Number
- CN202510984538.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-11-14
- Filing Date
- 2025-07-17
- Publication Date
- 2025-09-23
AI Technical Summary
Traditional data cables are easily worn out during frequent plugging and unplugging, resulting in insufficient wear resistance and affecting their service life.
By preparing a wear-resistant TPE material for data cables, tetramethylcyclotetrasiloxane and octafluoropentyl allyl ether are reacted under the action of chloroplatinic acid to form fluorinated cyclotetrasiloxane, which is then combined with reinforcing monomers and modified fillers to form a stable grid structure, thereby increasing the wear resistance and toughness of the material.
It improves the wear resistance and toughness of the data cable, prolongs its service life, and maintains good anti-bending performance.
Smart Images

Figure BDA0005503950940000131
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wear-resistant TPE material preparation, and in particular to a preparation method and application of a wear-resistant TPE material for a data cable. Background Art
[0002] With the popularization and diversification of electronic devices, data cables, as a common connection tool, are used more frequently and in a wider range of working environments. Traditional data cables, especially when connecting to mobile phones, tablets and other devices, often need to withstand certain friction and external forces due to frequent plugging and unplugging. Therefore, improving the durability and wear resistance of data cables has become the key to improving user experience and extending product life. TPE material, namely thermoplastic elastomer, is a material with high elasticity, high strength, and high resilience of rubber, and can be injection molded. It is environmentally friendly and non-toxic, has a wide range of hardness, and has excellent colorability, soft touch, and excellent weather resistance, fatigue resistance and temperature resistance. However, its wear resistance is not high. At this stage, the way to enhance wear resistance is to add wear-resistant fillers, but the addition of wear-resistant fillers reduces its bending resistance, thereby reducing its service life. Summary of the Invention
[0003] The purpose of the present invention is to provide a preparation method and application of a wear-resistant TPE material for a data cable, which solves the problem that the surface of the data cable will wear out or even break after long-term use.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing a wear-resistant TPE material for a data cable comprises the following steps:
[0006] Step A1: Tetramethylcyclotetrasiloxane, octafluoropentyl allyl ether, chloroplatinic acid and DMF are uniformly mixed, nitrogen protection is introduced, and the reaction is carried out at a speed of 120-150 r / min and a temperature of 70-80° C. for 3-5 hours to obtain fluorinated cyclotetrasiloxane. Octamethylcyclotetrasiloxane, fluorinated cyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen protection is introduced, and the reaction is carried out at a speed of 120-150 r / min and a temperature of 105-110° C. for 3-5 hours to obtain a reinforced monomer;
[0007] Step A2: Mix polytetramethylene glycol, isophorone diisocyanate, dibutyltin dilaurate and DMF, introduce nitrogen protection, and react for 2-3 hours at a speed of 60-80 r / min and a temperature of 75-80°C. Add reinforcing monomer and modified filler, react for 3-4 hours, then add ethylenediamine, react for 1-1.5 hours, heat to 100°C, keep warm for 1-1.5 hours, cool to 40-50°C, and keep warm for 10-15 hours to obtain a wear-resistant TPE material for data cables.
[0008] Furthermore, the molar ratio of tetramethylcyclotetrasiloxane and octafluoropentyl allyl ether described in step A1 is 1:4, the amount of chloroplatinic acid is 1‰ of the mass of octafluoropentyl allyl ether, and the molar ratio of octamethylcyclotetrasiloxane, fluorinated cyclotetrasiloxane, tetramethylammonium hydroxide, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.9:0.5:3:2.
[0009] Furthermore, the mass ratio of the polytetramethylene ether diol, isophorone diisocyanate, reinforcing monomer, modified filler and ethylenediamine described in step A2 is 12:42:20:5:5, the amount of dibutyltin dilaurate is 1.5% of the mass of isophorone diisocyanate, and the molecular weight of the polytetramethylene ether diol is 2000.
[0010] Furthermore, the modified filler is prepared by the following steps:
[0011] Step B1: Sodium imidazole, 3-chloropropyltrimethoxysilane and toluene are mixed, nitrogen is introduced, and the reaction is carried out at a speed of 200-300 r / min and a temperature of 10-15° C. for 3-5 hours to obtain a modified monomer. The modified monomer, isopropanol, sodium hydroxide and deionized water are mixed, and the reaction is carried out at a speed of 150-200 r / min and a temperature of 85-90° C. for 3-5 hours. After cooling to 20-25° C., the reaction is carried out for 10-15 hours to obtain functionalized cyclotetrasiloxane sodium tetrasiloxide;
[0012] Step B2: Methyldichlorosilane, allyl alcohol, chloroplatinic acid and DMF are mixed, nitrogen is introduced into the mixture, and the reaction is carried out for 8-10 hours at a speed of 120-150 r / min and a temperature of 70-80°C to obtain intermediate 1. Intermediate 1, 3-furoic acid, dicyclohexylcarbodiimide, 3A molecular sieve and toluene are introduced into the mixture under argon protection, and the reaction is carried out for 3-5 hours at a speed of 200-300 r / min and a temperature of 80-85°C to obtain a modifier. Functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine and tetrahydrofuran are mixed, stirred at a speed of 150-200 r / min and a temperature of 0°C, and the modifier is added. The reaction is carried out for 3-5 hours, and then the temperature is raised to 20-25°C and the reaction is carried out for 20-24 hours to obtain a functionalized cage-type silsesquioxane;
[0013] Step B3: dispersing graphene in ethanol, stirring and adding deionized water and KH550 at a speed of 200-300 r / min and a temperature of 60-70°C, and reacting for 2-3 hours to obtain pretreated graphene, mixing the pretreated graphene, maleic anhydride and DMF, reacting for 1-1.5 hours at a speed of 150-200 r / min and a temperature of 10-15°C, raising the temperature to 60-65°C, adding triethylamine, acetic anhydride and nickel acetate, and continuing the reaction for 2-3 hours to obtain modified graphene;
[0014] Step B4: The modified graphene, functionalized cage-type silsesquioxane, aluminum chloride and DMF are mixed evenly, and the reaction is carried out at a speed of 120-150 r / min and a temperature of 50-60°C for 8-10 hours to obtain a precursor. The precursor, 1-(3-aminopropyl)imidazole and methanol are mixed evenly, and the mixture is stirred at a speed of 200-300 r / min and a temperature of 30-40°C, and zinc chloride is added. The mixture is heated to 60-65°C and the reaction is carried out for 3-5 hours to obtain a modified filler.
[0015] Furthermore, the molar ratio of sodium imidazole and 3-chloropropyltrimethoxysilane in step B1 is 1:1, and the usage ratio of the modified monomer, isopropyl alcohol, sodium hydroxide and deionized water is 5 mmol:10 mL:6 mmol:5 mmol.
[0016] Furthermore, the molar ratio of methyldichlorosilane and allyl alcohol described in step B2 is 1:1, the amount of chloroplatinic acid is 1‰ of the mass of methyldichlorosilane, the molar ratio of intermediate 1, 3-furoic acid and dicyclohexylcarbodiimide is 1:1:1.1, the amount of 3A molecular sieve is 8% of the mass of 3-furoic acid, and the mass ratio of functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine, tetrahydrofuran and modifier is 20:4:40:5.
[0017] Furthermore, the amount of KH550 described in step B3 is 1% of the mass of graphene, and the amount ratio of pretreated graphene, DMF, maleic anhydride, triethylamine, acetic anhydride and nickel acetate is 5g:50mL:50mmol:5mL:12mL:3.5g.
[0018] Furthermore, the mass ratio of the modified graphene and the functionalized cage-type silsesquioxane described in step B4 is 3:1, the mass of aluminum chloride is 8‰ of the mass of the modified graphene, and the amount ratio of the precursor, 1-(3-aminopropyl)imidazole and zinc chloride is 1g:20mmo l:5mmo l.
[0019] The beneficial effects of the present invention are as follows: a wear-resistant TPE material for a data cable prepared by the present invention uses tetramethylcyclotetrasiloxane and octafluoropentyl allyl ether as raw materials, and under the action of chloroplatinic acid, the Si-H on the tetramethylcyclotetrasiloxane reacts with the double bond on the octafluoropentyl allyl ether to prepare fluorinated cyclotetrasiloxane, the octamethylcyclotetrasiloxane and the fluorinated cyclotetrasiloxane are ring-opened, and then polymerized with 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to prepare a reinforcing monomer, polytetramethylene ether diol and isophorone diisocyanate are reacted to form a polyurethane prepolymer, the reinforcing monomer and the modified filler are added, and the amino group on the reinforcing monomer and the amino group on the surface of the modified filler can extend the chain of the polyurethane prepolymer, and finally ethylenediamine is added to prepare the wear-resistant TPE material.
[0020] The modified filler uses sodium imidazole and 3-chloropropyltrimethoxysilane as raw materials, so that sodium imidazole is grafted onto the chlorine atom site on 3-chloropropyltrimethoxysilane to obtain a modified monomer, and the modified monomer is hydrolyzed and polycondensed to form functionalized sodium tetrasiloxane tetrasiloxide. Methyldichlorosilane and allyl alcohol react with the Si-H bond on methyldichlorosilane and the double bond on allyl alcohol under the action of chloroplatinic acid to obtain intermediate 1, and intermediate 1 and 3-furoic acid are esterified under the action of dicyclohexylcarbodiimide to react the hydroxyl group on intermediate 1 with the carboxyl group on 3-furoic acid to obtain a modifier, and the functionalized sodium tetrasiloxane tetrasiloxide reacts with the modifier to react the silicon on the functionalized sodium tetrasiloxane tetrasiloxide. Sodium alkoxide reacts with chlorine atom sites on a modifier to prepare a functionalized cage-type silsesquioxane, graphene is treated with KH550 to graft amino groups on the graphene surface to prepare pretreated graphene, the pretreated graphene is reacted with maleic anhydride to react the amino groups on the pretreated graphene with maleic anhydride to form maleimide to prepare modified graphene, the modified graphene and functionalized cage-type silsesquioxane are reacted with aluminum trichloride to react the maleimide on the functionalized graphene with the furan structure DA on the functionalized cage-type silsesquioxane to prepare a precursor, the precursor, 1-(3-aminopropyl)imidazole and zinc chloride are reacted to coat the surface of the precursor with imidazole zinc to prepare a modified filler.
[0021] The TPE material has a hyperbranched structure that can increase the mechanical properties of the material. The addition of modified fillers increases the cross-linking points of the TPE material, allowing the TPE material molecules to form a stable grid, thereby increasing the wear resistance of the TPE material. The addition of strengthening monomers embeds silicone segments and fluorocarbon segments in the molecular chain, increasing the hydrophobicity of the TPE molecules and improving the service life. A zinc organic framework is connected between the modified filler and the polyurethane prepolymer molecular chain, and the TPE material itself contains a six-membered ring structure, which enables the TPE material to adapt well to surface contact when worn, thereby reducing wear. The dynamic cross-linking of the modified filler and the TPE material molecules improves the toughness of the material, and does not significantly decrease the toughness due to the increase in cross-linking points, thereby increasing the bending resistance of the TPE material. DETAILED DESCRIPTION
[0022] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0023] Example 1: A method for preparing a wear-resistant TPE material for a data cable, comprising the following steps:
[0024] Step A1: Tetramethylcyclotetrasiloxane, octafluoropentyl allyl ether, chloroplatinic acid and DMF are uniformly mixed, nitrogen protection is introduced, and the reaction is carried out at a speed of 120 r / min and a temperature of 70° C. for 3 hours to obtain fluorinated cyclotetrasiloxane. Octamethylcyclotetrasiloxane, fluorinated cyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen protection is introduced, and the reaction is carried out at a speed of 120 r / min and a temperature of 105° C. for 3 hours to obtain a reinforced monomer;
[0025] Step A2: Mix polytetramethylene glycol, isophorone diisocyanate, dibutyltin dilaurate and DMF, introduce nitrogen protection, and react at a speed of 60 r / min and a temperature of 75°C for 2 hours. Add reinforcing monomer and modified filler, react for 3 hours, then add ethylenediamine, react for 1 hour, heat to 100°C, keep warm for 1 hour, cool to 40°C, and keep warm for 10 hours to obtain a wear-resistant TPE material for data cables.
[0026] The molar ratio of tetramethylcyclotetrasiloxane and octafluoropentyl allyl ether described in step A1 is 1:4, the amount of chloroplatinic acid is 1‰ of the mass of octafluoropentyl allyl ether, and the molar ratio of octamethylcyclotetrasiloxane, fluorinated cyclotetrasiloxane, tetramethylammonium hydroxide, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.9:0.5:3:2.
[0027] The mass ratio of the polytetramethylene ether diol, isophorone diisocyanate, reinforcing monomer, modified filler and ethylenediamine described in step A2 is 12:42:20:5:5, the amount of dibutyltin dilaurate is 1.5% of the mass of isophorone diisocyanate, and the molecular weight of the polytetramethylene ether diol is 2000.
[0028] The modified filler is prepared by the following steps:
[0029] Step B1: Sodium imidazole, 3-chloropropyltrimethoxysilane and toluene were mixed, nitrogen was introduced, and the reaction was carried out at a speed of 200 r / min and a temperature of 10°C for 3 hours to obtain a modified monomer. The modified monomer, isopropanol, sodium hydroxide and deionized water were mixed, and the reaction was carried out at a speed of 150 r / min and a temperature of 85°C for 3 hours. After that, the temperature was lowered to 20°C and the reaction was carried out for 10 hours to obtain functionalized sodium tetrasiloxide of cyclotetrasiloxane;
[0030] Step B2: Methyldichlorosilane, allyl alcohol, chloroplatinic acid and DMF were mixed, nitrogen was introduced into the mixture, and the reaction was carried out at a speed of 120 r / min and a temperature of 70°C for 8 hours to obtain intermediate 1. Intermediate 1, 3-furoic acid, dicyclohexylcarbodiimide, 3A molecular sieve and toluene were introduced into the mixture under argon protection, and the reaction was carried out at a speed of 200 r / min and a temperature of 110°C for 3 hours to obtain a modifier. Functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine and tetrahydrofuran were mixed, stirred at a speed of 150 r / min and a temperature of 0°C, and the modifier was added. The mixture was reacted for 3 hours, and then the temperature was raised to 20°C and the reaction was carried out for 20 hours to obtain a functionalized cage-type silsesquioxane.
[0031] Step B3: Graphene was dispersed in ethanol, stirred at a speed of 200 r / min and a temperature of 60°C, and deionized water and KH550 were added for reaction for 2 hours to obtain pretreated graphene. The pretreated graphene, maleic anhydride and DMF were mixed, and the reaction was carried out at a speed of 150 r / min and a temperature of 10°C for 1 hour. The temperature was raised to 60°C, triethylamine, acetic anhydride and nickel acetate were added, and the reaction was continued for 2 hours to obtain modified graphene.
[0032] Step B4: The modified graphene, functionalized cage-type silsesquioxane, aluminum chloride and DMF were mixed evenly, and the reaction was carried out at a speed of 120 r / min and a temperature of 50°C for 8 hours to obtain a precursor. The precursor, 1-(3-aminopropyl)imidazole and methanol were mixed evenly, and the mixture was stirred at a speed of 200 r / min and a temperature of 30°C, and zinc chloride was added. The mixture was heated to 60°C and reacted for 3 hours to obtain a modified filler.
[0033] The molar ratio of sodium imidazole and 3-chloropropyltrimethoxysilane in step B1 is 1:1, and the usage ratio of the modified monomer, isopropyl alcohol, sodium hydroxide and deionized water is 5 mmol:10 mL:6 mmol:5 mmol.
[0034] The molar ratio of methyldichlorosilane and allyl alcohol described in step B2 is 1:1, the amount of chloroplatinic acid is 1‰ of the mass of methyldichlorosilane, the molar ratio of intermediate 1, 3-furoic acid and dicyclohexylcarbodiimide is 1:1:1.1, the amount of 3A molecular sieve is 8% of the mass of 3-furoic acid, and the mass ratio of functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine, tetrahydrofuran and modifier is 20:4:40:5.
[0035] The amount of KH550 described in step B3 is 1% of the mass of graphene, and the amount ratio of pretreated graphene, DMF, maleic anhydride, triethylamine, acetic anhydride and nickel acetate is 5g:50mL:50mmo l:5mL:12mL:3.5g.
[0036] The mass ratio of the modified graphene and the functionalized cage-type silsesquioxane described in step B4 is 3:1, the mass of aluminum chloride is 8‰ of the mass of the modified graphene, and the amount ratio of the precursor, 1-(3-aminopropyl)imidazole and zinc chloride is 1g:20mmol:5mmo l.
[0037] Example 2: A method for preparing a wear-resistant TPE material for a data cable, comprising the following steps:
[0038] Step A1: Tetramethylcyclotetrasiloxane, octafluoropentyl allyl ether, chloroplatinic acid and DMF are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out at a speed of 120 r / min and a temperature of 75° C. for 4 hours to obtain fluorinated cyclotetrasiloxane. Octamethylcyclotetrasiloxane, fluorinated cyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and reaction 4 is carried out at a speed of 120 r / min and a temperature of 110° C. to obtain a reinforced monomer;
[0039] Step A2: Mix polytetramethylene glycol, isophorone diisocyanate, dibutyltin dilaurate and DMF, introduce nitrogen protection, and react for 2.5 hours at a speed of 60 r / min and a temperature of 80°C. Add reinforcing monomer and modified filler, react for 3 hours, then add ethylenediamine, react for 1.5 hours, heat to 100°C, keep warm for 1 hour, cool to 45°C, and keep warm for 13 hours to obtain a wear-resistant TPE material for data cables.
[0040] The molar ratio of tetramethylcyclotetrasiloxane and octafluoropentyl allyl ether described in step A1 is 1:4, the amount of chloroplatinic acid is 1‰ of the mass of octafluoropentyl allyl ether, and the molar ratio of octamethylcyclotetrasiloxane, fluorinated cyclotetrasiloxane, tetramethylammonium hydroxide, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.9:0.5:3:2.
[0041] The mass ratio of the polytetramethylene ether diol, isophorone diisocyanate, reinforcing monomer, modified filler and ethylenediamine described in step A2 is 12:42:20:5:5, the amount of dibutyltin dilaurate is 1.5% of the mass of isophorone diisocyanate, and the molecular weight of the polytetramethylene ether diol is 2000.
[0042] The modified filler is prepared by the following steps:
[0043] Step B1: Sodium imidazole, 3-chloropropyltrimethoxysilane and toluene were mixed, nitrogen was introduced for protection, and the reaction was carried out at a speed of 300 r / min and a temperature of 10°C for 4 hours to obtain a modified monomer. The modified monomer, isopropanol, sodium hydroxide and deionized water were mixed, and the reaction was carried out at a speed of 150 r / min and a temperature of 90°C for 4 hours. After that, the temperature was lowered to 25°C and the reaction was carried out for 10 hours to obtain functionalized sodium tetrasiloxide of cyclotetrasiloxane;
[0044] Step B2: Methyldichlorosilane, allyl alcohol, chloroplatinic acid and DMF were mixed, nitrogen was introduced into the mixture, and the reaction was carried out at a speed of 150 r / min and a temperature of 75°C for 9 hours to obtain intermediate 1. Intermediate 1, 3-furoic acid, dicyclohexylcarbodiimide, 3A molecular sieve and toluene were introduced into the mixture under argon protection, and the reaction was carried out at a speed of 200 r / min and a temperature of 115°C for 4 hours to obtain a modifier. Functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine and tetrahydrofuran were mixed, stirred at a speed of 200 r / min and a temperature of 0°C, and the modifier was added. The mixture was reacted for 4 hours, and then the temperature was raised to 25°C and the reaction was carried out for 24 hours to obtain a functionalized cage-type silsesquioxane;
[0045] Step B3: Graphene was dispersed in ethanol, stirred at a speed of 200 r / min and a temperature of 65°C, and deionized water and KH550 were added for a reaction of 3 hours to obtain pretreated graphene. The pretreated graphene, maleic anhydride and DMF were mixed and reacted at a speed of 150 r / min and a temperature of 15°C for 1 hour. The temperature was raised to 65°C, triethylamine, acetic anhydride and nickel acetate were added, and the reaction was continued for 2 hours to obtain modified graphene.
[0046] Step B4: The modified graphene, functionalized cage-type silsesquioxane, aluminum chloride and DMF were mixed evenly, and the reaction was carried out at a speed of 150 r / min and a temperature of 55°C for 9 hours to obtain a precursor. The precursor, 1-(3-aminopropyl)imidazole and methanol were mixed evenly, and the mixture was stirred at a speed of 200 r / min and a temperature of 35°C, and zinc chloride was added. The mixture was heated to 65°C and reacted for 4 hours to obtain a modified filler.
[0047] The molar ratio of sodium imidazole and 3-chloropropyltrimethoxysilane in step B1 is 1:1, and the usage ratio of the modified monomer, isopropyl alcohol, sodium hydroxide and deionized water is 5 mmol:10 mL:6 mmol:5 mmol.
[0048] The molar ratio of methyldichlorosilane and allyl alcohol described in step B2 is 1:1, the amount of chloroplatinic acid is 1‰ of the mass of methyldichlorosilane, the molar ratio of intermediate 1, 3-furoic acid and dicyclohexylcarbodiimide is 1:1:1.1, the amount of 3A molecular sieve is 8% of the mass of 3-furoic acid, and the mass ratio of functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine, tetrahydrofuran and modifier is 20:4:40:5.
[0049] The amount of KH550 described in step B3 is 1% of the mass of graphene, and the amount ratio of pretreated graphene, DMF, maleic anhydride, triethylamine, acetic anhydride and nickel acetate is 5g:50mL:50mmol:5mL:12mL:3.5g.
[0050] The mass ratio of the modified graphene and the functionalized cage-type silsesquioxane described in step B4 is 3:1, the mass of aluminum chloride is 8‰ of the mass of the modified graphene, and the amount ratio of the precursor, 1-(3-aminopropyl)imidazole and zinc chloride is 1g:20mmol:5mmo l.
[0051] Example 3: A method for preparing a wear-resistant TPE material for a data cable, comprising the following steps:
[0052] Step A1: Tetramethylcyclotetrasiloxane, octafluoropentyl allyl ether, chloroplatinic acid and DMF are uniformly mixed, nitrogen protection is introduced, and the reaction is carried out at a speed of 150 r / min and a temperature of 80° C. for 5 hours to obtain fluorinated cyclotetrasiloxane. Octamethylcyclotetrasiloxane, fluorinated cyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen protection is introduced, and the reaction is carried out at a speed of 150 r / min and a temperature of 110° C. for 5 hours to obtain a reinforced monomer;
[0053] Step A2: Mix polytetramethylene glycol, isophorone diisocyanate, dibutyltin dilaurate and DMF, introduce nitrogen protection, and react at a speed of 80 r / min and a temperature of 80°C for 3 hours. Add reinforcing monomer and modified filler, react for 4 hours, then add ethylenediamine, react for 1.5 hours, heat to 100°C, keep warm for 1.5 hours, cool to 50°C, and keep warm for 15 hours to obtain a wear-resistant TPE material for data cables.
[0054] The molar ratio of tetramethylcyclotetrasiloxane and octafluoropentyl allyl ether described in step A1 is 1:4, the amount of chloroplatinic acid is 1‰ of the mass of octafluoropentyl allyl ether, and the molar ratio of octamethylcyclotetrasiloxane, fluorinated cyclotetrasiloxane, tetramethylammonium hydroxide, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.9:0.5:3:2.
[0055] The mass ratio of the polytetramethylene ether diol, isophorone diisocyanate, reinforcing monomer, modified filler and ethylenediamine described in step A2 is 12:42:20:5:5, the amount of dibutyltin dilaurate is 1.5% of the mass of isophorone diisocyanate, and the molecular weight of the polytetramethylene ether diol is 2000.
[0056] The modified filler is prepared by the following steps:
[0057] Step B1: Sodium imidazole, 3-chloropropyltrimethoxysilane and toluene were mixed, nitrogen was introduced, and the reaction was carried out at a speed of 300 r / min and a temperature of 15° C. for 5 hours to obtain a modified monomer. The modified monomer, isopropanol, sodium hydroxide and deionized water were mixed, and the reaction was carried out at a speed of 200 r / min and a temperature of 90° C. for 5 hours. After that, the temperature was lowered to 25° C. and the reaction was carried out for 15 hours to obtain functionalized sodium cyclotetrasiloxane tetrasiloxide;
[0058] Step B2: Methyldichlorosilane, allyl alcohol, chloroplatinic acid and DMF were mixed, nitrogen was introduced into the mixture, and the reaction was carried out at a speed of 150 r / min and a temperature of 80°C for 10 hours to obtain intermediate 1. Intermediate 1, 3-furoic acid, dicyclohexylcarbodiimide, 3A molecular sieve and toluene were introduced into the mixture under argon protection, and the reaction was carried out at a speed of 300 r / min and a temperature of 120°C for 5 hours to obtain a modifier. Functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine and tetrahydrofuran were mixed, stirred at a speed of 200 r / min and a temperature of 0°C, and the modifier was added. The mixture was reacted for 5 hours, and then the temperature was raised to 25°C and the reaction was carried out for 24 hours to obtain a functionalized cage-type silsesquioxane;
[0059] Step B3: Graphene was dispersed in ethanol, stirred at a speed of 300 r / min and a temperature of 70°C, and deionized water and KH550 were added for a reaction of 3 hours to obtain pretreated graphene. The pretreated graphene, maleic anhydride and DMF were mixed and reacted at a speed of 200 r / min and a temperature of 15°C for 1.5 hours. The mixture was heated to 65°C, triethylamine, acetic anhydride and nickel acetate were added, and the reaction was continued for 2-3 hours to obtain modified graphene.
[0060] Step B4: The modified graphene, functionalized cage-type silsesquioxane, aluminum chloride and DMF were mixed evenly, and the reaction was carried out at a speed of 150 r / min and a temperature of 60°C for 10 hours to obtain a precursor. The precursor, 1-(3-aminopropyl)imidazole and methanol were mixed evenly, and the mixture was stirred at a speed of 300 r / min and a temperature of 40°C, and zinc chloride was added. The mixture was heated to 65°C and reacted for 5 hours to obtain a modified filler.
[0061] The molar ratio of sodium imidazole and 3-chloropropyltrimethoxysilane in step B1 is 1:1, and the usage ratio of the modified monomer, isopropyl alcohol, sodium hydroxide and deionized water is 5 mmol:10 mL:6 mmol:5 mmol.
[0062] The molar ratio of methyldichlorosilane and allyl alcohol described in step B2 is 1:1, the amount of chloroplatinic acid is 1‰ of the mass of methyldichlorosilane, the molar ratio of intermediate 1, 3-furoic acid and dicyclohexylcarbodiimide is 1:1:1.1, the amount of 3A molecular sieve is 8% of the mass of 3-furoic acid, and the mass ratio of functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine, tetrahydrofuran and modifier is 20:4:40:5.
[0063] The amount of KH550 described in step B3 is 1% of the mass of graphene, and the amount ratio of pretreated graphene, DMF, maleic anhydride, triethylamine, acetic anhydride and nickel acetate is 5g:50mL:50mmo l:5mL:12mL:3.5g.
[0064] The mass ratio of the modified graphene and the functionalized cage-type silsesquioxane described in step B4 is 3:1, the mass of aluminum chloride is 8‰ of the mass of the modified graphene, and the amount ratio of the precursor, 1-(3-aminopropyl)imidazole and zinc chloride is 1g:20mmol:5mmo l.
[0065] Comparative Example 1: Compared with Example 1, this comparative example does not add a reinforcing monomer, and the remaining steps are the same.
[0066] Comparative Example 2: Compared with Example 1, this comparative example uses phenyltrimethoxysilane instead of the modified monomer, and the remaining steps are the same.
[0067] Comparative Example 3: Compared with Example 1, this comparative example uses pretreated graphene instead of modified filler, and the remaining steps are the same.
[0068] Comparative Example 4. Compared with Example 1, this comparative example uses 1-(3-aminopropyl)imidazole and methanol to mix evenly, stir and add zinc chloride at a speed of 200 r / min and a temperature of 30°C, raise the temperature to 60°C, and react for 3 hours. The obtained product replaces the modified filler, and the remaining steps are the same.
[0069] Comparative Example 5: Compared with Example 1, this comparative example uses functionalized cage-type silsesquioxane instead of the precursor, and the remaining steps are the same.
[0070] The TPE materials prepared in Examples 1-3 and Comparative Examples 1-5 were tested for wear resistance according to the standard of GB / T3960-2016. According to the standard of GB / T1040.1-2018, 30 mm × 5 mm × 2 mm specimens were prepared and the tensile strength was tested at a tensile rate of 5 mm / min. The test results are shown in Table 1 below.
[0071] Table 1
[0072]
[0073] It can be seen from the above table that the present invention has excellent toughness while maintaining good wear resistance.
[0074] The above content is merely an example and explanation of the concept of the present invention. Those skilled in the art may make various modifications or additions to the described specific embodiments or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a wear-resistant TPE material for a data cable, characterized by: The specific steps include: Step A1: Tetramethylcyclotetrasiloxane, octafluoropentyl allyl ether, chloroplatinic acid and DMF are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out to obtain fluorinated cyclotetrasiloxane; octamethylcyclotetrasiloxane, fluorinated cyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out to obtain a reinforcing monomer; Step A2: polytetramethylene glycol, isophorone diisocyanate, dibutyltin dilaurate and DMF are mixed, nitrogen is introduced for protection, and a reaction is carried out. A reinforcing monomer and a modified filler are added, and after the reaction, ethylenediamine is added and a reaction is carried out. The temperature is increased and maintained, and then the temperature is decreased and maintained to obtain a wear-resistant TPE material for a data cable.
2. The method for preparing a wear-resistant TPE material for a data cable according to claim 1, characterized in that: The molar ratio of tetramethylcyclotetrasiloxane and octafluoropentyl allyl ether described in step A1 is 1:4, and the molar ratio of octamethylcyclotetrasiloxane, fluorinated cyclotetrasiloxane, tetramethylammonium hydroxide, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.9:0.5:3:
2.
3. The method for preparing a wear-resistant TPE material for a data cable according to claim 1, characterized in that: The mass ratio of the polytetramethylene ether glycol, isophorone diisocyanate, reinforcing monomer, modified filler and ethylenediamine described in step A2 is 12:42:20:5:
5.
4. The method for preparing a wear-resistant TPE material for a data cable according to claim 1, characterized in that: The modified filler is prepared by the following steps: Step B1: Sodium imidazole, 3-chloropropyltrimethoxysilane, and toluene are mixed and reacted under nitrogen protection to obtain a modified monomer. The modified monomer, isopropyl alcohol, sodium hydroxide, and deionized water are mixed and reacted, and the temperature is lowered to obtain functionalized sodium cyclotetrasiloxane tetrasiloxide. Step B2: Methyldichlorosilane, allyl alcohol, chloroplatinic acid, and DMF are mixed and reacted under nitrogen protection to obtain intermediate 1. Intermediate 1, 3-furoic acid, dicyclohexylcarbodiimide, 3A molecular sieve, and toluene are reacted under argon protection to obtain a modifier. Functionalized cyclotetrasiloxane sodium tetrasilanolate, triethylamine, and tetrahydrofuran are mixed and stirred, and the modifier is added. After reacting, the temperature is increased and the reaction is continued to obtain a functionalized cage-type silsesquioxane. Step B3: dispersing graphene in ethanol, stirring, adding deionized water and KH550, and reacting to obtain pretreated graphene; mixing the pretreated graphene, maleic anhydride, and DMF, reacting the mixture, heating, adding triethylamine, acetic anhydride, and nickel acetate, and continuing the reaction to obtain modified graphene; Step B4: Modified graphene, functionalized cage-type silsesquioxane, aluminum chloride and DMF are mixed and reacted to obtain a precursor, the precursor, 1-(3-aminopropyl)imidazole and methanol are mixed and stirred, zinc chloride is added, and the temperature is raised to react to obtain a modified filler.
5. The method for preparing a wear-resistant TPE material for a data cable according to claim 4, characterized in that: The molar ratio of sodium imidazole and 3-chloropropyltrimethoxysilane in step B1 is 1:1, and the usage ratio of the modified monomer, isopropyl alcohol, sodium hydroxide and deionized water is 5 mmol:10 mL:6 mmol:5 mmol.
6. The method for preparing a wear-resistant TPE material for a data cable according to claim 4, characterized in that: The molar ratio of methyldichlorosilane and allyl alcohol described in step B2 is 1:1, the molar ratio of intermediate 1,3-furoic acid and dicyclohexylcarbodiimide is 1:1:1.1, and the mass ratio of functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine, tetrahydrofuran and modifier is 20:4:40:
5.
7. The method for preparing a wear-resistant TPE material for a data cable according to claim 4, characterized in that: The amount of KH550 described in step B3 is 1% of the mass of graphene, and the amount ratio of pretreated graphene, DMF, maleic anhydride, triethylamine, acetic anhydride and nickel acetate is 5g:50mL:50mmol:5mL:12mL:3.5g.
8. The method for preparing a wear-resistant TPE material for a data cable according to claim 4, characterized in that: The mass ratio of the modified graphene and the functionalized cage-type silsesquioxane described in step B4 is 3:1, and the amount ratio of the precursor, 1-(3-aminopropyl)imidazole and zinc chloride is 1g:20mmo l:5mmo l.
9. An application of wear-resistant TPE material for data cables, characterized by: The wear-resistant TPE material prepared by the method according to any one of claims 1 to 8 is used to prepare a data cable.
Citation Information
Cited By
Wear-resistant network cable with high shielding effectiveness and preparation method thereof
CN121537778A
A high shielding effectiveness wear-resistant mesh wire and a preparation method thereof
CN121537778B
